Constitutional Criminal Law and Gender Approach: Judging with a Gender Perspective - Altabe, Martha Helia (2024)
The study analyzes the effects of the control of constitutionality and conventionality in the Argentine system, in light of the international systems for the protection of human rights and the legal instruments to which the Argentine State is a signatory. These systems do not have derogatory effects on domestic norms, but the inapplicability of these to the specific case and the possibility of providing for actions or omissions; that is, orders to do or not to do with respect to a specific situation in order to safeguard the principle of constitutional and conventional supremacy, so that the subjective right enshrined in these hierarchically superior norms prevails. In this perspective, the aforementioned systems of rights are of mandatory and preferential application to any domestic legislation of lower rank. In other words, it is not only the text of the covenants, conventions and treaties, but also the jurisprudence of the Inter-American Court of Human Rights, its advisory opinions, declarations and resolutions, as well as the reports, recommendations and resolutions of the Inter-American Commission on Human Rights, which can even issue precautionary measures, as well as the pronouncements, recommendations and reports of the United Nations agencies. Consequently, judges must make the necessary efforts to ensure that comprehensive reparation measures in cases of gender-based violence are based on a transformative approach; that is, that they contribute to the elimination of the patterns of discrimination and marginalization that may have been the cause of the victimizing events.